Marcinkiewicz积分在加权Campanato空间上的有界性(Marcinkiewicz integrals on weighted Campanato spaces) - SIZeng-yan(司增艳); JIANGYin-sheng(江寅生) (Zhejiang Daxue xuebao. Lixue ban, 2008)
The Marcinkiewicz integrals are class of important operators in analysis and are widely studied. The boundedness of the Marcinkiewicz integral operator on certain weighted Campanato spaces is estiblished.